Explanation:
Taking the provided equation ,
1) Here denominator of two fractions are 5 and x +3 . So their LCM will be 5(x+3)
![\implies ((x+3)(3x+4)-(2)(5))/(5(x+3))=(8)/(5)](https://img.qammunity.org/2022/formulas/mathematics/college/qppn7ncu5012sodf9vhz9bgn8sficsjyni.png)
2) Transposing 5(x+3) to Right Hand Side . And 5 to Left Hand Side .
![\implies 5(3x^2+4x+9x+12 -10) = 40(x+3)](https://img.qammunity.org/2022/formulas/mathematics/college/qbvc8sjfyqfp844g2cjelg5o274aypg5qa.png)
3) Multiplying the expressions.
![\implies 5(3x^2+13x+2) = 40x + 120](https://img.qammunity.org/2022/formulas/mathematics/college/358a8lr4tyeukiu9114snsnvtaw59ylohd.png)
4) Opening the brackets .
![\implies 15x^2+ 65x + 10 = 40x + 120](https://img.qammunity.org/2022/formulas/mathematics/college/dvx7ce3a80mb0vnbu8e7doo57hdpnbultl.png)
5) Transposing all terms to Left Hand Side .
![\implies 15x^2 + 65x - 40x + 10 - 120 = 0 \\\\\implies 15x^2 +25x - 110 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/gdl2y5gwrhz5nlplto6smp61uahl79rrj4.png)
6) Solving the quadratic equation .
![\implies 5(3x^2+5x -22) = 0 \\\\\implies 3x^2+13x-22 = 0 \\\\ \implies x = (-b\pm √(b^2-4ac))/(4ac) \\\\\implies x = (-5\pm √(5^2-4(-22)(3)))/(2(3)) \\\\\implies x = (-5\pm √(289))/(6)\\\\\implies x =(-5\pm 17)/(6) \\\\\implies x = (17-5)/(6),(-17-5)/(6)\\\\\implies x = (12)/(6),(-22)/(6) \\\\\underline{\boxed{\red{\bf\implies x = 2 , (-11)/(3)}}}](https://img.qammunity.org/2022/formulas/mathematics/college/2i2ck6tt2ib1p0cuul0grtzx1mqrg7s40i.png)